Sustainable Agriculture: Strategies for Achieving Sustainable Agriculture and Financial Success (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Eco food production must shift its focus from output to profit in light of the new agriculturalreality. In the context of sustainable agriculture research, striking a balance between financial return eco- design can be attained through a thorough examination of both inputs and outcomes. Though difficult,the current direction in research should be directed toward methods that can actually achieve this delicatebalancing act. Agriculture is essential to the survival of all species on Earth. Agriculture has an impact onevery aspect of human life, from the air we breathe to the fossil fuels we use.The future of humanitydepends on progress in sustainable agriculture. In a larger sense, agricultural sustainability refers toenvironmental sustainability. In this article, we have compiled a variety of strategies proven to increasefarm output, income, and longevity.